Changes in MicroRNAs Expression and Clinical Associations in Patients with Neuroendocrine Pancreatic Tumors - Tavano, Francesca; di Mola, Fabio Francesco; Burbaci, Francesca Paola; Lombardi, Lucia; Copetti, Massimiliano; Piepoli, Ada; Andriulli, Angelo; Maiello, Evaristo; di Sebastiano, Pierluigi (JOP. Journal of the Pancreas, 2012)
Context In a previously study, we analyzed associations between altered expression of 13 microRNAs (miR-145, miR-23a, miR-455-3p, miR-708, miR-151-5p, miR-30c, miR-let-7i, miR-199a-5p, miR-30a, miR-143, miR-21, miR-155*, and miR-31) and clinical variables in patients with pancreatic adenocarcinoma. Objective Here, expression levels of these miRNAs were analyzed to evaluate their possible associations with clinical-pathological features in patients underwent surgical resection for pancreatic neuroendocrine tumors (PETs). Methods miRNAs expression levels in tumors compared to matched-pairs non-cancerous tissue samples, were analyzed by using TaqMan MicroRNA Assay. Association analysis was performed by means of Spearman correlation coefficient and Mann-Whitney U-test. Results No significant association was found between miR-145, miR-23a, miR-455-3p, and miR-708 levels and patients sub-phenotypes. Conversely, miR-151-5p expression was inversely correlated with age at diagnosis (rs=-0.77, P=0.009), both miR-30a and miR-let-7i levels were positively associated with tumor size (rs=0.69, P=0.027 and rs=0.67, P=0.034), while over-expression of either miR-199a-5p and miR-30c was associate with male gender (P=0.046 and P=0.003). Further original finding was the association between miR-143, miR-21 and miR-155* levels and tumor mitotic index (P=0.04, P=0.0002, and P<0.0001, respectively), while expression of both miR-31 and miR-30c was associated with tumor proliferation index (P=0.003 and P=0.01, respectively). In addition, miRNAs expression levels were also found to be correlated with each others in PETs tissue samples. Conclusions These data suggest a prognostic significance for specific miRNAs in PETs. Understanding the associations between miRNAs expression levels could help identify novel regulatory network involved biology of PETs.